Perioperative Management of Patients with Hemophilia during Spinal Surgery - Kobayashi, Kazuyoshi (Asian Spine J, 2018)
STUDY DESIGN: Single-center retrospective study. PURPOSE: To optimize the perioperative management of patients with hemophilia who are undergoing spinal surgery. OVERVIEW OF LITERATURE: Hemophilia is a rare disease in which there is a tendency of bleeding because of a congenital deficiency in blood coagulation factor activity. There has been no previous report on spinal surgery in patients with hemophilia. METHODS: The subjects were five patients (all males) with hemophilia who underwent spinal surgery at Nagoya University Hospital. Two patients had hemophilia A (deficiency of factor VIII) and three had hemophilia B (deficiency of factor IX). The mean age at the time of surgery was 63 years (range, 46–73 years). The following surgeries were performed: posterior lumbar interbody fusion (PLIF) in two patients, and lumbar fenestration, cervical laminoplasty and lumbar fenestration, and cervical laminoplasty and PLIF in one patient each. RESULTS: Coagulation factor at a mean dose of 4.8 ×10(3) U (range, 3–6 ×10(3) U) was intravenously injected before surgery, and a mean dose of 5.2 ×10(3) U (rang, 4–6 ×10(3) U) was continuously administered for 24 hours after surgery. Factor activity was maintained at ≥80% until postoperative day 14 and at ≥50% thereafter. The average duration of surgery was 178 minutes (range, 133–233 minutes), the estimated blood loss was 661 mL (range, 272–1,344 mL), and a drain tube was left subfascially in place for 2 days in all patients. Reoperation due to postoperative surgical site infection was required in one patient, but there were no complications due to hemorrhagic diathesis. The total dose of coagulation factor administered during hospitalization was 102 ×10(3) U (range, 46–198 ×10(3) U). CONCLUSIONS: Coordination with a hematologist and dose adjustment of the coagulation factor preparation to maintain a target level of coagulation factor activity facilitated a smooth postoperative course with perioperative control of bleeding during spinal surgery for patients with hemophilia.